PENGEMBANGAN BUKU AJAR MATA KULIAH BIOTEKNOLOGI BERBASIS KEARIFAN LOKAL DAERAH TABAGSEL - Batubara, Melvariani Syari; Lubis, Mutiara (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2022)
The research background is that learning biotechnology courses for biology teacher candidate students in order to achieve optimal results requires a carefully prepared and applicative learning media. The objectives achieved in this study were to determine the results of textbook products based on local wisdom in the Tabagsel area based on expert validation of learning media and biotechnology materials, the results of peer-to-peer trials of the Prodi Biologi UMTS, the results of individual trials, groups. small, and the field is limited. The method used in this research is included in development research. The results of this study indicate that the textbook products of Biotechnology subject matter based on local wisdom of the Tabagsel area based on the validation of learning media experts, the average percentage score is 76%, including in the "feasible" category, the Biotechnology material expert, the percentage of the average score is 82.5 % included in the "feasible" category, the lecturer's peer trial total percentage of the average score was 78% included in the "feasible" category, individual trials the total percentage of the average score was 74% included in the "quite feasible" category. small group try out the percentage average score was 71.6% included in the "quite feasible" category, and limited field trials the number of percentage mean scores was 82% included in the "decent" category. The conclusion of this study that the textbook products developed are included in the valid category to be applied in biotechnology lectures. The contribution of this research is that it can contribute to the repertoire of thoughts for the development of science related to the development of textbooks for Biotechnology courses based on local wisdom of the Tabagsel area.